Best Estimate Selection Bias in the Value of a Statistical Life. Issue 2 (9th October 2017) - Viscusi, W. Kip
Abstract : Selection of the best estimates of economic parameters frequently relies on the "best estimates" or a meta-analysis of the "best set" of parameter estimates from the literature. Using an all-set dataset consisting of all reported estimates of the value of a statistical life (VSL) as well as a best-set sample of the best estimates from these studies, this article estimates statistically significant publication selection biases in each case. Biases are much greater for the best-set sample, as one might expect, given the subjective nature of the best-set selection process. For the all-set sample, the mean bias-corrected estimate of the VSL for the preferred specification is 8.1 million for the whole sample and 11.4 million based on the CFOI data, while for the best-set results, the whole sample value is 3.5 million, and the CFOI data estimate is 4.4 million. Previous estimates of huge publication selection biases in the VSL estimates are attributable to these studies' reliance on best-set samples.